REVIEW PERSAMAAN BLACK-SCHOLES FRAKSIONAL DIMODIFIKASI: Review The Modified Fractional Black-Scholes Equation - Sugandha, Agus (Universitas Perwira Purbalingga, 2021)
This paper will discuss the solution of the fractional Black-Scholes equation which is a general form of the Black-Scholes equation and the novelty of research on the modified Black-Scholes equation. The methods for finding solutions to the fractional Black Scholes equation have been written in many international journals. The solution to the fractional Black Scholes equation in this case is reviewed by the Fractional Calculus approach. With the Fractional Calculus approach, the solution process in finding solutions to the Fractional Black Scholes equation becomes more efficient. Some of the methods used to find solutions to the Fractional Black Scholes Equation include the Sumudu transformation method, the series expansion method, the Homotopy perturbation method, the Adomian decomposition method, and the Laplace Adomian decomposition method.